Wpływ systemów informatycznych klasy ERP na proces fuzji i przejęć - Gąsior-Żarska, Aleksandra (Impact of Computer Systems of the ERP Class on the Process of the Merger and Acquisition, 2005)
The article could afford showing of information and communication of significance on the purpose in efficient management with the company with the special consideration of processes of the merger and acquisition. Systems of the ERP class are one of tools assisting this process. Unremitting development of the economy based on knowledge is contributing companies to distributing this system in order improving management. It is necessary to underline that high expenses subjects have to take which aren't scaring the manager personnel away already from putting systems of the ERP class into practice by virtue of anticipated benefits. It is counting especially in companies realizing the M&A process which are aiming at standardizing and the comparability of obtained information in newly for resultant unit.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1081, s. 106-113